Effect of aerobic high-intensity interval training on leg strength in cross country skiers - Cetin, E.; Yarym, I.; Ates, B. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Competitive cross-country skiing has recently experienced rapid changes, with the addition of several new racing forms. The increase in the speed factor in races puts forward the importance of strength among other motoric features of the neuromuscular apparatus (Sandbakk, 2011). The purpose of this study was to assess the effect of 2km uphill training on leg strength.